Provenance Shifts During Neogene Brahmaputra Delta Progradation Tied to Coupled Climate and Tectonic Change in the Eastern Himalaya. (16th December 2021) - Betka, Paul M.; Thomson, Stuart N.; Sincavage, Ryan; Zoramthara, C.; Lalremruatfela, C.; Lang, Karl A.; Steckler, Michael S.; Bezbaruah, Devojit; Borgohain, Pradip; Seeber, Leonardo
Abstract: The Bengal Basin preserves the erosional signals of coupled tectonic‐climatic change during late Cenozoic development of the Himalayan orogen, yet regional correlation and interpretation of these signals remains incomplete. We present a new geologic map of fluvial‐deltaic deposits of the Indo‐Burman Ranges (IBR), five detrital zircon fission track analyses, and twelve high‐n detrital zircon U‐Pb age distributions (dzUPb) from the Barail (late Eocene–early Miocene), Surma (early–late Miocene), and Tipam (late Miocene–Pliocene) Groups of the ancestral Brahmaputra delta. We use dzUPb statistical tests to correlate the IBR units with equivalent age strata throughout the Bengal Basin. An influx of trans‐Himalayan sediment and the first appearance of ∼50 Ma grains of the Gangdese batholith in the lower Surma Group (∼18–15 Ma) records the early Miocene arrival of the ancestral Brahmaputra delta to the Bengal Basin. Contributions from Himalayan sources systematically decrease up section through the late Miocene as the contribution of Trans‐Himalayan Arc sources increases. The Miocene (∼18–8 Ma) deposition of the Surma Group records upstream expansion of the ancestral Brahmaputra River into southeastern Tibet. Late Miocene (<8 Ma) progradation of the fluvial part of the delta (Tipam Group) routed trans‐Himalayan sediment over the shelf edge to the Nicobar Fan. We propose that Miocene progradation of the ancestral Brahmaputra delta reflects increasing rates of erosion and sea level fall during intensification of the South Asian Monsoon after the Miocene Climate Optimum, contemporaneous with a pulse of tectonic uplift of the Himalayan hinterland and Tibet. Plain Language Summary: The development of mountain topography is a balance between forces that push them up (plate tectonics) and processes of erosion which break them down (climate). The Himalayan Mountains formed over the past 50 million years and their growth is attributed to tectonic and climate interactions between the India‐Asia plate collision and development of monsoon conditions over south Asia. This paper examines a nearly complete record of sedimentary rocks that were eroded from various Himalayan sources and deposited in the ancestral Brahmaputra delta between ∼30 and ∼5 million years ago. We present sediment age data to date and correlate the deposits, as well as identify Himalayan sources that contributed sediment to the delta. Prior to a middle Miocene warm period, most sediment was sourced from the frontal ranges of the Himalaya, like the modern Ganges watershed. After the middle Miocene, when South Asian Monsoon conditions intensified, the watershed expanded north of the Himalayan divide and delivered increasingly large proportions of sediment from Tibet, like the modern Brahmaputra watershed. Middle Miocene intensification of monsoon conditions, combined with a synchronous pulse of tectonic activity, led to a major expansion of the Brahmaputra delta, the largest depositional system on Earth today. Key Points: Neogene Indo‐Burman strata are quantitatively correlated with the Siwalik Group and Bengal‐Nicobar fan using dzUPb age distributions dzUPb provenance trends are regionally consistent, recording initial influx of trans‐Himalayan sediment with ∼18–8 Ma deposition of the Surma Group Middle to late Miocene progradation of the Brahmaputra delta reflects coupled climate‐tectonic change during intensification of South Asian Monsoon